Examining the role of innovation in enhancing the performance of agritourism enterprises and agricultural farms in Albania - Tomorri, Ilir; Kurtaj, Denisa; Baraku, Brunilda; Çulani, Adela; Domi, Fabjola (Edelweiss Applied Science and Technology, 2025)
Innovation is considered a key driver for agricultural transformation and rural development, especially in the context of developing countries. The purpose of this study is to examine the role of innovation in the performance of agritourism enterprises and agricultural farms in Albania. The methodology used for this paper focused on the collection and analysis of data from questionnaires in 12 regions of the country, through face-to-face interviews with 672 respondents. The data were analyzed and processed with the SPSS program, in accordance with the purpose and research objectives of the study. The results from the respondents’ responses show that innovation plays a critical role in increasing the performance and competitiveness of agricultural farms and agritourism enterprises, improving efficiency and productivity, diversification of activities, cost reduction, and increased income. The data show that the barriers and drivers that affect the adoption of innovation in the agricultural sector in Albania are costs of implementing technologies, access to financing, risk and uncertainty in investment returns, lack of necessary digital infrastructure, lack of knowledge and professional skills of farmers, and support from public institutions. The study findings highlight the importance of collaboration among stakeholders (policymakers, public agencies, academic institutions, etc.) in drafting policies and strategies to foster the implementation of innovation in the rural sector.